Evaluating pharmacist independent prescribing for patients with mental illness in community care: a qualitative study - Alsaeed, Bashayr A.; Hall, Jason; Keers, Richard N. (Frontiers in Psychiatry, 2025)
BackgroundNon-medical prescribing by pharmacists, nurses, and other professionals has been introduced over recent decades to address staff shortages and the growing demand for mental health services globally. However, most of the emerging evidence concerning the contribution and impact of non-medical prescribing focuses on nurses, despite the expanding role of pharmacists.AimThe study aimed to explore in depth the factors influencing implementation and delivery of pharmacist non-medical prescribing services for patients with mental illness in community-based settings across the UK.MethodRemote semi-structured interviews were conducted with pharmacist independent prescribers across the UK between January and June 2024. Participants were recruited using purposive sampling through the research team’s professional networks and social media platforms, with data transcribed and analysed thematically.Results20 pharmacist prescribers were interviewed, including six from general practice and seven from specialist mental health care. Four main themes, including insecurity, training/education, ambiguity, and workload management were identified. Lack of confidence in prescribing was reported by most participants – general practice based pharmacists cited challenges related to a lack of confidence in managing patients with mental health illness, whereas those in specialist services identified difficulties with risk management. Concerns about training and education were frequently raised by participants, including inadequacies in the undergraduate pharmacy curriculum and non-medical prescribing courses in preparing them for key elements of practice related to mental health care such as assessing patients with mental illness. Pharmacist prescribers also reported challenges with workload management and role clarity. While pharmacists anecdotally perceived high patient satisfaction with the care they provided, this was not reported to be formally evaluated.ConclusionSeveral factors were identified that influenced successful implementation and delivery of pharmacist prescribing services for patients with mental illness in community care. Improved education and training in mental health along with a clearer definition of the pharmacist prescribing role may support optimal service delivery. Future work evaluating pharmacist prescribing should explore the viewpoints of patients and carers in order to develop holistic improvement recommendations driven by key stakeholders.